Exosomal PD-L1 derived from hypoxia nasopharyngeal carcinoma cell exacerbates CD8+ T cell suppression by promoting PD-L1 upregulation in macrophages - Xiaofei Yuan; Xiong Liu; Di Jiang; Zijun Zheng; Xuemin Ma; Shuting Wu; Xiangping Li; Juan Lu; Ming Fu (Cancer Immunology, Immunotherapy)
Abstract Immunotherapy targeting the programmed death ligand-1/programmed cell death protein-1 (PD-L1/PD-1) pathway exhibits limited effectiveness in individuals with recurrent and metastatic nasopharyngeal carcinoma (NPC). Recent studies have noted that hypoxia within the tumor microenvironment (TME) triggers intricate interplay, termed “hypoxia-induced exosome-mediated communication”, between cancer cells and various immune cells. However, the role of hypoxia in modulating the immunosuppressive environment and its implications on the efficacy of immunotherapy in NPC remains poorly understood. In this study, we found hypoxia inducible factor-1 (HIF-1α) was positively associated with increased PD-L1 levels and decreased CD8+ T cell infiltration, and correlated with a poor prognosis. Mechanistically, we demonstrated that hypoxia regulated the expression of PD-L1 in NPC cells and their exosomes by activating the binding of HIF-1α to the PD-L1 promoter. Meanwhile, using in vitro approaches, we found that macrophages could upregulate their PD-L1 expression through the phagocytosis of exosomal PD-L1 derived from NPC cells. Furthermore, we confirmed that PD-L1+ macrophages could induce CD8+ T cell exhaustion and reduce their proliferation. In conclusion, our study revealed that hypoxia (via HIF-1α) upregulated the expression of PD-L1 in exosomes derived from NPC cells, while macrophages induce the suppression of CD8+ T cells by phagocytosis of exosomal PD-L1. Targeting the PD-L1+ macrophages could potentially serve as a promising approach to augment the effectiveness of immune checkpoint blockade in NPC.